2018
DOI: 10.1177/0306624x18769602
|View full text |Cite
|
Sign up to set email alerts
|

Examining Individual Characteristics and Program Performance to Understand Two-Year Recidivism Rates Among Drug Court Participants: Comparing Graduates and Terminators

Abstract: Drug courts strive to break the cycle of substance use and crime by providing community-based treatment and rehabilitation. The purpose of the present study was to (a) identify significantly different factors between program participants (i.e., graduates/terminators) that may affect recidivism and (b) examine these significant individual and program performance factors associated with two-year recidivism. Secondary data were examined for a stratified random sample of drug court participants ( N = 534). Examini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…The relative failure of imprisonment as a period of forced abstinence and the high rates of recidivism among drug-dependent offenders was inspiration for the establishment of the world’s first drug court in Miami-Dade County, Florida, in the late 1980s. Since then, drug courts have proliferated internationally (Cooper, 2003; Payne, 2006, 2008; Shannon et al, 2018), and the guiding principle of therapeutic jurisprudence (Hora et al, 1998; Spencer, 2012) has made a solid mark on criminal justice systems worldwide. In Australia, the diversion and treatment of drug users is organized on a continuum (see Wundersitz, 2007 for an overview) from the early intervention and diversion of low-level users to the intensive court-supervised drug court programs that are offered as a last resort alternative to imprisonment.…”
Section: Introductionmentioning
confidence: 99%
“…The relative failure of imprisonment as a period of forced abstinence and the high rates of recidivism among drug-dependent offenders was inspiration for the establishment of the world’s first drug court in Miami-Dade County, Florida, in the late 1980s. Since then, drug courts have proliferated internationally (Cooper, 2003; Payne, 2006, 2008; Shannon et al, 2018), and the guiding principle of therapeutic jurisprudence (Hora et al, 1998; Spencer, 2012) has made a solid mark on criminal justice systems worldwide. In Australia, the diversion and treatment of drug users is organized on a continuum (see Wundersitz, 2007 for an overview) from the early intervention and diversion of low-level users to the intensive court-supervised drug court programs that are offered as a last resort alternative to imprisonment.…”
Section: Introductionmentioning
confidence: 99%
“…No previous research has examined how sanctions imposed while in the domestic court impact later rates of recidivism, yet there is some evidence from drug treatment courts that jail sanctions may increase recidivism. Shannon et al (2016) examined defendant and processing factors in a drug treatment court and found that participants who were given a jail sanction for noncompliance were more likely to recidivate than those who were not sanctioned in this manner. Other research, however, finds no relationship between jail sanctions and recidivism in drug treatment courts (Sheeran & Heideman, 2021), or more importantly, the incenstives should be used more than sanctions to facilitate compliance (e.g., Wodahl et al, 2011).…”
Section: Judicial Court Monitoring and Recidivismmentioning
confidence: 99%
“…Similarly, findings from Krebs et al (2007) indicated that Hispanic/Latino participants had a higher likelihood of re-arrest following drug court than White participants. Yet, there are still several evaluations that have determined race was not a primary influence on post-drug court outcomes (Cissner et al 2013;Rossman et al 2011;Shannon et al 2018).…”
Section: Disparities In Post-program Outcomesmentioning
confidence: 99%